The story of Nandigram - Batabyal, Somnath (Continuum, 2012)
This paper is an ethnographic exploration of two television news channels, Star News in Hindi and Star Ananda in Bengali, part of Rupert Murdoch's burgeoning media empire in India. It seeks to explore two basic questions: in the world of private television news, who are the producers and who is their audience. Through these questions, it tries to understand the fundamentals of the news business; the intricate links that exist between ratings, audience groups, the journalist's news sense and content. It explores corporate policies in television organizations, which in pursuit of advertising revenue, not only curtail editorial independence but editorial imagination. I claim that despite the proliferation of news channels, the economics of the industry enforces a hegemonic class based articulation of content. This suppresses all other possible constructs and promotes a unitary vision of an affluent nationhood; an India articulated by the middle classes for themselves.